High frequency isolated bidirectional dual active bridge DC-DC converters and its application to distributed energy systems: an overview - Kiran Bathala; Dharavath Kishan; Nagendrappa Harischandrappa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Among the DC-DC converters, an isolated bidirectional dual active bridge converter is a core circuit for high-frequency power converters in distributed energy system applications. These high-frequency power conversion systems attract academia and industry due to various advantages, such as high-power density, less weight, reduced noise, high efficiency, low cost and high reliability. First, the importance of power electronic converters in modern-day life is introduced. Second, a topological overview of voltage-fed and current-fed isolated bidirectional dual active bridge converters is presented with their importance in integrating hybrid power sources. Third, switching modes of isolated bidirectional DC-DC converters are also presented with a degree of freedom of control.  Forth, performance evaluation of voltage-fed and current-fed isolated bidirectional converters has been presented with an example. Their suitability in integrating fuel cells and photovoltaics with energy storage systems in low to medium-power applications is presented.